Properties of Controlled Low-Strength Material Mixes Made from Wastepaper Sludge Ash and Recycled Fine Aggregate - Fauzi, Mohd Azrizal; Arshad, Mohd Fadzil; Md Nor, Noorsuhada; Kiai, Setphen (International Journal of Integrated Engineering, 2021)
As demarcated in the American Concrete Institute (ACI 229R-13), CLSM stands for controlled low-strength material, which is a self-consolidating cementitious material that can be used as a backfill instead of compacted fill. However, the usage of CLSM in the construction industry was limited to backfilling, structural filling, void filling, and erosion control due to low compressive strength. On the other hand, using materials that can replace the material responsible for greenhouse gases has been promoted globally to halt the incidence of global warming instigated by releasing greenhouse gases, mainly CO2, into the atmosphere. Waste paper sludge ash (WPSA) is one among them, and researchers have discovered that it can be used to substitute cement in the manufacture of CLSM effectively. In this research, CLSM were made using recycled fine aggregate (RFA) as fine aggregate and WPSA as cement replacement to determine the plastic and in-services properties of CLSM mixes made from both materials mentioned. For the plastic properties, the test included are flowability, bleeding and hardening test as for in-services properties, including the testing of density and compressive strength of CLSM produced. The testing of CLSM in terms of plastic and in-services properties was influenced by the water-to-cementitious ratio, WPSA replacement and total cementitious material. The flowability of CLSM is influenced by the amount of RFA and WPSA used in the design. The lower the water absorption, the more water will be absorbed and gives less bleeding. Therefore, different proportions of w/cm, WPSA replacement and total cementitious material of CLSM mixtures influence a product's plastic in-service properties. Its compressive strength was between 0.3 MPa to 4 MPa, which satisfied the backfill strength required by ACI 229R-13, and it can also be concluded that samples with higher cement content show higher compressive strength results than others.